International law of the sea (2015) - Tanaka, Yoshifumi (2015)
"This new edition has been fully revised and updated to include the contemporary issues together with new cases delivered by international courts and tribunals, such as the ICJ, ITLOS and Arbitral Tribunals, treaties, UN resolutions, and other instruments. It retains the clear chapter structure of the first edition, but has expanded the topics on marine spaces beyond national jurisdiction, maritime delimitation, protection of the marine environment. A new concluding chapter has also been included and presents a perspective on the future development of the international law of the sea. Detailed footnotes and further reading sections, combined with illustrations and tables ensure understanding of the subject. By offering clarity of expression and academic rigour, The International Law of the Sea remains the best choice for students"--
The law of the sea in perspective -- Baselines and related issues -- Marine spaces under national jurisdiction I : territorial sovereignty -- Marine spaces under national jurisdiction II : sovereign rights -- Marine spaces beyond national jurisdiction -- Maritime delimitation -- Conservation of marine living resources -- Protection of the marine environment -- Conservation of marine biological diversity -- Marine scientific research -- Maintenance of international peace and security at sea -- Land-locked and geographically disadvantaged states -- Peaceful settlement of international disputes.
Includes bibliographical references and index.
Keywords: Convention on the law of the sea; Law of the sea; 86.80 international law: general; 86.93 maritime law; LAW -- International; Droit de la mer; 2; Conventions internationales; Environnement marin; Ressources de la mer; Protection de l'environnement.; Recherche marine; Law of the sea; Seerecht; 2